Brosur Digital untuk Fitur Eksterior Produk Otomotif berbasis Markerless Augmented Reality - Suharso, Aries; Haerul Jaman, Jajam; Mulyana, Alex (Jurnal Teknologi Terpadu, 2020)
Traditionally, brochures are widely used in the delivery of information about a product. Along with technological developments, this brochure can be developed into an interactive digital brochure by implementing markerless augmented reality methods so that application content can interact with the environment. The test results using the rating scale obtained assessment aspects of the display included in the category of very good (130.75), aspects of the content included in the good category (129.75) and in total classified as very good (130.25). This shows that the digital brochure application developed is quite good and can be useful both for Automotive product marketers and for consumers.